Preparation and characterization of ZrB2 and TaC containing Cf/SiC composites via Polymer-Infiltration-Pyrolysis process. Issue 5 (May 2017) - Uhlmann, Franziska; Wilhelmi, Christian; Schmidt-Wimmer, Stephan; Beyer, Steffen; Badini, Claudio; Padovano, Elisa
Abstract: To improve the thermo-chemical resistance of PIP–Cf /SiC composites, the SiC matrix is modified by adding ZrB2 and Ta powder to the pre-ceramic slurry to form Cf /SiC–ZrB2 –TaC composites. Within this study the modified composites are investigated regarding their microstructure, chemical composition and physical properties (density = 2, 39–2, 72 g/cm 3 ; porosity = 20, 3–24, 8 vol.-%; fiber volume content = 52–57 vol.-%). Mechanical properties are investigated in order to ensure that there is no negative influence by ZrB2 and TaC matrix modification. The matrix modification is followed by an improvement in bending strength (up to 27% increase), Young's modulus (up to 28% increase) and for interlaminar shear strength (up to 22% increase). Finally the thermo-chemical behavior of the Cf /SiC–ZrB2 –TaC composites is evaluated in a combustion chamber-like environment using the Airbus Group long-term material test facility (Environmental Relevant Burner Rig-Kerosene, ERBURIG K ). The results show that the thermo-chemical resistance of Cf /SiC–ZrB2 –TaC composites is improved and the oxygen permeability through the composite is decreased (from 5 to 1 layer).